2018
DOI: 10.1016/j.jpor.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The single mandibular implant study – Short-term effects of the loading protocol on Oral Health-related Quality of Life

Abstract: The single mandibular implant concept was associated with a positive impact on quality of life. However, no statistically significant influence of implant loading on quality of life was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 12 publications
2
39
1
Order By: Relevance
“…It is also assumed to be a more feasible option for geriatric patients due to their reduced functional demands and the favourable local bone condition in the symphyseal region that ensures satisfactory primary implant stability. Previous clinical studies reported favourable results on patient satisfaction and dental patient‐reported outcomes measures, 6,7 independently of the implant loading protocol, 8 as well as other clinical and radiographic outcomes such as implant survival rate, marginal bone loss and longitudinal implant stability 9 . Despite differences across clinical studies regarding their experimental design, implant and retention systems, loading protocols and selected outcomes, there is convincing evidence on the marked improvements provided by the IOD compared to the conventional treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is also assumed to be a more feasible option for geriatric patients due to their reduced functional demands and the favourable local bone condition in the symphyseal region that ensures satisfactory primary implant stability. Previous clinical studies reported favourable results on patient satisfaction and dental patient‐reported outcomes measures, 6,7 independently of the implant loading protocol, 8 as well as other clinical and radiographic outcomes such as implant survival rate, marginal bone loss and longitudinal implant stability 9 . Despite differences across clinical studies regarding their experimental design, implant and retention systems, loading protocols and selected outcomes, there is convincing evidence on the marked improvements provided by the IOD compared to the conventional treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Liddelow and Henry (6) reported 100% survival rate after three-year observation period for all implants loaded immediately at the day of implant placement. The present results could be compared to 82% implant survival rate in the studies published by Kronström et al who observed that immediately loaded implants failed within the first twelve months (18,20). The slightly higher implant failure rate occurred in Kronström et al (18,20) studies may be attributed to implant overloading by laboratory inaccuracies, as the researchers did not intra-orally relate the implant components to the denture.…”
Section: Discussionmentioning
confidence: 45%
“…Although good clinical results have been reported for immediate loading on ball attachments, (3,5,6,12,15,(18)(19)(20) studies available for reliable data on immediately loaded locator attachments are limited in the literature (11). Therefore, the aim of this study was to assess primarily the influence of locator attachment on the initial stability and bone height changes for immediately loaded SIMO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results corroborate previous studies that described a relevant improvement in OHRQoL after implant placement under existing RDPs. 5 However, this conversion technique entails lower costs for the patient.…”
Section: Discussionmentioning
confidence: 99%